Clinical and epidemiological characteristics of workers diagnosed with COVID-19 in the setting of an external occupational safety and health service in Lima-Peru - Palomino Baldeón , Juan Carlos (2022)
Objective: To describe the clinical and epidemiological characteristics of workers kept under occupational medical surveillance conducted by an occupational safety and health service. Materials and methods: An observational, descriptive, retrospective, longitudinal study of a group of workers diagnosed with COVID-19 kept under occupational medical surveillance from March 18 to July 31, 2020. The data was analyzed using the Stata Statistical Software: Release 15. Results: Males were more severely affected than females (77.16 %), among which the 20- to 39-year-old age group prevailed (63.30 %). On the other hand, study subjects with no comorbidities accounted for 81.11 %. However, the remaining 18.9 % presented one or more comorbidities, with obesity being the most frequent one (61.95 %), followed by asthma (11.09 %). Sore throat and cough were the most common symptoms with 20.67 % and 19.78 %, respectively. Conclusions: The study population mainly consisted of young male adults with no comorbidities, who neither showed predominant symptoms nor required hospitalization.